2021
DOI: 10.1177/2164956120982956
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of a Yogic Breathing Technique on the Well-Being of Healthcare Professionals During the COVID-19 Pandemic

Abstract: Background The COVID-19 pandemic has created unprecedented challenges for healthcare globally, the brunt of which has been borne by the health care providers (HCPs). These challenges are felt more keenly in India, as they stretch an insufficiently resourced healthcare system. The long hours, cross over of responsibilities, lack of resources to adequately care for patients, and concerns around safety of self and loves ones, have led to a spike in anxiety, depression, insomnia and other stress – related disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 39 publications
3
63
0
1
Order By: Relevance
“…Some of the common practices in this field are meditation and yoga and our study has also revealed a better emotional state related to these practices. These results are in line with the benefits suggested by online yoga or mindfulness meditation programs ( Divya et al, 2021 ; Jasti et al, 2020 ; Luberto et al, 2020 ; Matiz et al, 2020 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Some of the common practices in this field are meditation and yoga and our study has also revealed a better emotional state related to these practices. These results are in line with the benefits suggested by online yoga or mindfulness meditation programs ( Divya et al, 2021 ; Jasti et al, 2020 ; Luberto et al, 2020 ; Matiz et al, 2020 ).…”
Section: Discussionsupporting
confidence: 88%
“…A recent review discussed the association between physical activity and mental health during the pandemic ( Violant-Holz et al, 2020 ). A few studies suggested positive effects of online yoga and mindfulness meditation programs on well-being and reduction of stress during the COVID-19 outbreak ( Divya et al, 2021 ; Jasti et al, 2020 ; Luberto et al, 2020 ; Matiz et al, 2020 ). However, the relation between practicing yoga, mindfulness or meditation and mental health during the pandemic has been in inconsistent in surveys ( Conversano et al, 2020 ; Jiménez et al, 2020 ; Vogel et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, introducing Yoga in the healthcare system would be beneficial for the patients, HCWs, and other service providers: they may successfully cope with psychological stress (34)(35)(36)(37). Stress, anxiety, and depression among HCWs in COVID-19 pandemic was reduced by practicing Sudarshan kriya (38). Perceived stress in COVID-19 patients was also reduced by multimedia psychoeducational intervention, which included relaxation and mindfulness techniques (39).…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, as proposed by Huppert et al (2009), well-being is a multifaceted concept. Comprehensive well-being indicators have been used to better understand the beneficial effects of regular yoga (e.g., Divya et al, 2021;Moszeik et al, 2020). However, few studies have looked into the effects of hot yoga, a particular style of yoga that is now gaining a lot of attention (Clarke et al, 2015).…”
Section: Article In Pressmentioning
confidence: 99%
“…and inertia (Khalsa et al, 2012), decrease mood disturbance and anxiety (Noggle et al, 2012), reduce depression in older adults (Patel et al, 2012), enhance resilience to workplace stress (Hartfiel et al, 2011), and even improve school performance in adolescents (Frank et al, 2017). A number of RCT and cross-sectional studies have demonstrated the effects of regular yoga on indicators of comprehensive well-being (e.g., Divya et al, 2021;Moszeik et al, 2020;Sahni et al, 2021). However, to the best of our knowledge, no RCT studies with a sufficiently large sample size have evaluated the effects of hot yoga on a comprehensive range of indicators of well-being, including mindfulness, peace of mind, mental health, flourishing, satisfaction with life, general health, and hedonic and eudaimonic well-being.…”
Section: Article In Pressmentioning
confidence: 99%